![]()
|
|||||||
The Analytical Scheme Base. 1/Мета-A_Маc-A. 2/Мета-A_Маc-B. 3/Мета-A_Маc-C(a). 4/Мета-A_Маc-C(b). 1_1/Мета-A_Маc-A_Маc-s-A. 2/Мета-A_Маc-A_Маc-s-B. 3/Мета-A_Маc-A_Маc-s-C(a). 4/Мета-A_Маc-A_Маc-s-C(b). 2_1/Мета-A_Маc-B_Маc-s-A. 2/Мета-A_Маc-B_Маc-s-B. 3/МThe Analytical Scheme Base \: |K: Metathesis | – large structure – repeated structure – cadenza structure 1/Мета-A_Маc-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-A_Маc-B `` A [m]+`` B [m]= C[ABC(ab)] 3/Мета-A_Маc-C(a) `` A [m]+`` B [m]= C[ABC(ab)] 4/Мета-A_Маc-C(b) `` A [m]+`` B [m]= C[ABC(ab)] ------------- 1_1/Мета-A_Маc-A_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-A_Маc-A_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-A_Маc-A_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-A_Маc-A_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)] 2_1/Мета-A_Маc-B_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-A_Маc-B_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-A_Маc-B_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-A_Маc-B_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)] 3_1/ Мета-A_Маc-C(a)_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-A_Маc-C(a)_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-A_Маc-C(a)_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-A_Маc-C(a)_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)] 4_1/Мета-A_Маc-C(b)_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-A_Маc-C(b)_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-A_Маc-C(b)_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-A_Маc-C(b)_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)]
|K: Meta-antithesis | – large structure – repeated structure – cadenza structure 1/Мета-B_Маc-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-B_Маc-B `` A [m]+`` B [m]= C[ABC(ab)] 3/Мета-B_Маc-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-B_Маc-C(b) `` A [m]+`` B [m]= C[ABC(ab)] ------------ 1_1/Мета-B_Маc-A_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-B_Маc-A_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-B_Маc-A_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-B_Маc-A_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)] 2_1/Мета-B_Маc-B_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-B_Маc-B_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-B_Маc-B_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-B_Маc-B_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)] 3_1/ Мета-B_Маc-C(a)_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-B_Маc-C(a)_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-B_Маc-C(a)_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-B_Маc-C(a)_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)]
4_1/Мета-B_Маc-C(b)_Маc-s-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-B_Маc-C(b)_Маc-s-B `` A [m]+`` B [m]= C{ab} 3/Мета-B_Маc-C(b)_Маc-s-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-B_Маc-C(b)_Маc-s-C(b) `` A [m]+`` B [m]= C[ABC(ab)] : / - repeat these dialectic structures
\:
|K: Metasynthesis, 1-st part|
– large structure – repeated structure – cadenza structure
1/Мета-C(a)_Маc-A `` A [m]+`` B [m]= C[ABC(ab)] 2/Мета-C(a)_Маc-B `` A [m]+`` B [m]= C[ABC(ab)] 3/Мета-C(a)_Маc-C(a) `` A [m]+`` B [m]= C{ab} 4/Мета-C(a)_Маc-C(b) `` A [m]+`` B [m]= C[ABC(ab)] ---------------
|
|||||||
|